DETERMINATION OF INFRASTRUCTURE, ATTRACTIVENESS AND SERVICE QUALITY TOWARDS TOURIST INTEREST THROUGH TOURISM PROMOTION IN KARIMUN REGENCY - Ahadian Zulseptriadi; Ngaliman; Muammar Khaddafi3 (CV. Radja Publika, 2024)
The Karimun Regency Tourism Office is trying to increase tourist interest in visiting Karimun Regency, including by improving the quality of community services in the tourism sector. However, information data was found that there was a negative impact on the level of tourist visits to Karimun Regency, among other things, due to problems with inadequate infrastructure, inadequate attractiveness of tourist destinations, service quality and tourism development not being supported by increasingly intensive and widespread regional promotion. This quantitative research aims to examine the determinants related to these factors on the interest of visiting tourists. It was concluded that there was a significant positive determination of infrastructure, service quality directly on tourist interest and tourism promotion in Karimun Regency. There is a significant positive determination of facilities and service quality directly on tourist interest. There is a negative but not significant determination of tourist attraction directly on tourist interest and tourism promotion. There is a positive and significant direct determination of tourism promotion on tourists' interest in visiting Karimun Regency. There is a significant positive determination of infrastructure and service quality in moderating tourism promotion on tourist interest in visiting Karimun Regency. There is a negative but not significant determination of tourist attraction in the moderation of tourism promotion on tourist interest in visiting Karimun Regency. It is recommended, among other things, to maximize exploration of uniqueness, diversity, completeness of information, facilities, network accessibility, hygiene and security services, as well as optimizing community involvement in developing tourist destinations in Karimun Regency. Optimizing tourism promotion through digital advertising, print, events, community participation and offering convenience policies.